BACTERIOLOGIC PROFILE AND ANTIBIOGRAM OF PAEDIATRIC BLOOD CULTURES IN A TERTIARY CARE CENTRE - MENAL GUPTA; UMA CHAUDHARY (International Journal of Pharma and Bio Sciences, 2015)
Bloodstream infections and sepsis are a common cause of morbidity and mortality in neonates and children. Blood culture provides the definitive diagnosis with identification of the causal organism and its antibiotic susceptibility. The etiologic agents are seen to vary between regions as well as over time. In this prospective study, 17.3% culture positivity was seen in blood culture samples from paediatric patients, with maximum isolation in neonatal age-group. Gram negative bacteraemia was more common than gram positive bacteraemia. S. aureus and P. aeruginosa were the most frequent isolates and showed a high degree of resistance to most drugs, including second line antibiotics. These results reveal the upsurge of multidrug resistance in paediatric patients and highlight the need for stringent regulation of antibiotic prescription.